Răspuns :
[ ( 100 - y x 10) ; 10 +5 ] x 10 =10 x 10
[ ( 100- y x 10 ) :10 + 5 ] x 10 =100
( 100 - y x 10 ) ; 10+ 5=100 ; 10
( 100 - y x 10) : 10 + 5 =10
( 100 - y x 10) : 10 =10 - 5
( 100- y x 10 ) : 10 = 5
100 - y x 10=5 x 10
100 - y x 10 =50
y x 10 =100- 50
y x 10 =50
y=50 : 10
y = 5
[(100-yx10):10+5]x10=20
[(100-yx10):10+5]=20:10
[(100-yx10):10+5]=2
(100-yx10):10+5=2
(100-yx10):10=2-5
(100-yx10):10=2-5
(100-yx10):10=-3
(100-yx10)=-3x10
100-yx10=-30
-yx10=-30-100
-yx10=-130
yx10=130
y=130:10
y=13
[(100-yx10):10+5]=20:10
[(100-yx10):10+5]=2
(100-yx10):10+5=2
(100-yx10):10=2-5
(100-yx10):10=2-5
(100-yx10):10=-3
(100-yx10)=-3x10
100-yx10=-30
-yx10=-30-100
-yx10=-130
yx10=130
y=130:10
y=13